2020
DOI: 10.1371/journal.pone.0227768
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of p-Akt, p-mTOR and p-eIF4E proteins associates with metastasis and unfavorable prognosis in non-small cell lung cancer

Abstract: The Akt (protein kinase B)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…The mTOR signaling pathway is an important pathway that is activated in multiple pathological processes and is thereby involved in tumor survival, proliferation and distant metastasis [ 16 ]. Deregulation of the mTOR pathway is observed in various cancers [ 17 , 18 ]. It has also been reported that the mTOR pathway regulates angiogenesis by modulating VEGF gene expression [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mTOR signaling pathway is an important pathway that is activated in multiple pathological processes and is thereby involved in tumor survival, proliferation and distant metastasis [ 16 ]. Deregulation of the mTOR pathway is observed in various cancers [ 17 , 18 ]. It has also been reported that the mTOR pathway regulates angiogenesis by modulating VEGF gene expression [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, conflicting evidence exists for non-small cell lung cancer (NSCLC). Thus, Lu and colleagues provided evidence for the overexpression of pAKT being associated with metastasis and poor prognosis by processing 341 NSCLC samples [ 32 ]. On the contrary, Shah and co-workers reported on pAKT as a favorable prognostic factor despite being associated with a high tumor grade in the analysis of 82 NSCLC specimens [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The active form of MNK1, p-MNK1 (Thr197/202), and phosphorylated eIF4E, p-eIF4E, are increased in lung cancer and correlate with poor overall survival of NSCLC patients [131,66]. In addition, high levels of p-MNK1 might act as an independent poor prognostic biomarker for these patients [66].…”
Section: Mnk In Lung Cancermentioning
confidence: 99%